Improving efficiency of quantum key distribution with probabilistic measurements. (2016) - Parakh, Abhishek; Verma, Pramode; Subramaniam, Mahadevan
The first part of this paper presents two efficient cryptographic protocols, based on quantum entanglement, for secure exchange of secret keys. While the first protocol requires storage of entangled qubits, the second protocol has no storage requirements and presents a probabilistic model. We show that there is a tradeoff between security against eavesdropping and the efficiency of the protocol in terms of usable bits available for the secret key. This security parameter s can be varied by the communicating parties based on practical considerations. In the second part of the paper, we apply the probabilistic model to BB84 and show how it can be used to improve the efficiency of BB84.